The Characteristics of female students in Allied Health Sciences Institution who performed routine breast self-examination (BSE) in Indonesia and Pakistan - Siti Khuzaiyah; Muhammad Tayyeb; Nuniek Nizmah Fajriyah (Universitas Muhammadiyah Pekajangan Pekalongan, 2023)
Breast cancer is a major public health concern worldwide. The incidence of breast cancer remains high. The mortality rate and prognosis for breast cancer can be improved with early diagnosis and therapy. Self-examination of the breasts is a common method of early diagnosis for women's health issues. This study aimed to explore the characteristics of female students in Allied Health Sciences Institution who performed regular breast self-examination in Indonesia and Pakistan. After institutional ethics review board approval and informed consent, a quantitative survey recruited 430 female students from Allied Health Sciences institutions in Indonesia and Pakistan. This study strictly followed the highest level of ethical standards proposed by Helsinki Declaration (Revised 2013). A closed and open-ended questionnaire was used to collect data on their demographics and characteristics. The questionnaire was distributed online using a google form. Data were analyzed using descriptive analytics . The findings of this study showed that n=395(91.86%) were aged 18-35 years, and 51% were from rural. 49% from urban areas. The majority of participants were single or never married (88%). Most participants were undergraduate students (95.35%). Almost half participants did routine BSE once a month (48.6%). Only 16% were very confident about doing a breast self-examination. Nearly half respondents had never seen a doctor (47%). A positive attitude was seen among all the students. Additionally, most students performed a weekly breast examination. Evidently, more than half of the participants lacked self-assurance when it came to performing a breast assessment. We found a significant percentage who had never been to a doctor for medical attention. Public campaigns to raise awareness and urge female student in allied health science to regularly see their doctors and engage in BSE are so crucial